Edukasi Latihan Prenatal Yoga pada Ibu Hamil sebagai Upaya Mengurangi Kecemasan dan Optimalisasi Posisi Janin - Arlym, Lisa Trina; Nursasmita, Rizqi; Lomrah, Siti (Universitas Baiturrahim, 2024)
Hormonal, anatomical and mechanical changes in pregnant women cause various kinds of complaints in pregnant women. Yoga during pregnancy provides benefits to physical, mental health and fetal position. The aim of this community service is to increase understanding and knowledge of pregnant women about prenatal yoga and to practice prenatal yoga movements to reduce anxiety and optimize fetal position. The service methods applied were education, prenatal yoga practice, qualitative evaluation and discussion. Activities will be carried out on 19 and 26 November 2023 at TPMB Jeanne Depok. The community service activity was attended by 10 pregnant women. The results of the community service activities were that all participants understood the benefits of prenatal yoga and most participants said their bodies felt better, sleeping became comfortable. It was concluded that after education and prenatal yoga practice it could be understood and provide benefits to the mothers.